2012
DOI: 10.1017/s0950268812001112
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HPAI H5N1 viruses in ducks sampled from live bird markets in Vietnam

Abstract: In Vietnam, highly pathogenic avian influenza (HPAI) H5N1 infections in poultry often occur without concomitant clinical signs and outbreaks are not consistently reported. Live bird markets represent a convenient site for surveillance that does not rely on farmers' notifications. Two H5N1 surveys were conducted at live bird markets/slaughter points in 39 districts (five provinces) in the Red River, Mekong delta, and central Vietnam during January and May 2011. Oropharyngeal and rectal swab samples from 12 480 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…26 The LBMs surrounding Phnom Penh have been established as foci for poultry movement in the country 18,27 and a previous market surveillance study in 2011 revealed a high rate of influenza A/H5N1 circulation in this setting. 25 To our knowledge, AIVs were detected in Cambodian LBMs during 2013 at a higher frequency than any other study published previously, 25,[28][29][30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 53%
“…26 The LBMs surrounding Phnom Penh have been established as foci for poultry movement in the country 18,27 and a previous market surveillance study in 2011 revealed a high rate of influenza A/H5N1 circulation in this setting. 25 To our knowledge, AIVs were detected in Cambodian LBMs during 2013 at a higher frequency than any other study published previously, 25,[28][29][30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 53%
“…For example, during the 2‐year period October 2012–September 2014, 13 confirmed HPAI H5N1 outbreaks were reported from 8 of 13 provinces of the Mekong Delta region (FAO, ). In contrast to this low frequency of disease outbreaks, HPAI H5N1 viruses are consistently detected in poultry flocks in the Mekong Delta and other regions of Vietnam (Phan et al., ; Nguyen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Birds of different types and from different geographic areas are introduced daily into LBMs and might be caged together, promoting local transmission of multiple virus subtypes and generating opportunities for reassortment (10)(11)(12). Surveys and routine surveillance have described the abundance and diversity of avian influenza A viruses (AIVs) in LBMs in AIV-endemic countries, including Bangladesh (1,4,11,(13)(14)(15)(16)(17)(18)(19)(20)(21). However, only the proportion of positive samples is usually reported, without accounting for the hierarchical data structure, especially the clustering of sampled poultry per LBM.…”
mentioning
confidence: 99%